Leading undergraduate provision in further education colleges: the experiences of BA Education programme leaders (UCL Press, 2023)
This article explores the experiences of those who lead undergraduate education-related programmes in further education (FE) colleges in England. Questionnaire and interview fieldwork with 14 further education-based programme leaders were supplemented by a comparison survey of equivalent professionals from higher education institutions (HEIs). Drawing on Hodgson and Spours's four-level lifelong learning ecology and Nardi and O'Day's keystone species concept, our analysis characterises the role of the undergraduate programme leader as distinctive and critical within the further education context. Extremely multifaceted and busy, this role is also poorly defined, often involving individuals relying on craft wisdom accrued within specific contexts. Three overall strands of responsibility emerged in participants' view of their role: the administrative and organisational demands of colleges and the validation/franchising of higher education partners; the provision to learners of appropriate support in their studies; and the recognition of and response to pastoral needs of students. Tensions were identified between these, with one strand tending to preoccupy programme leaders at any time, obscuring their view of other important role objectives. As such, we introduce the concept of sightlines to capture the importance of enabling programme leaders to see through and beyond their institutional context and engage outwards, rather than turn inwards. Practical recommendations include the provision of time and licence to study for advanced qualifications, to undertake research and to help nurture distinctive cultures of higher education learning.